COVID-19 Pandemic and Its Gendered Impact on Indian Physicians - Sabita Jiwnani; Priya Ranganathan; Virendra Tiwari; Apurva Ashok; Devayani Niyogi; George Karimundackal; C. S. Pramesh (JCO Global Oncology, 2021)
PURPOSEThe 2018 WHO health workforce report analyzing gender equity in 104 countries reported that although women constituted 70% of the workers, they were less likely to be employed full-time and faced a 28% gender pay gap. The ongoing COVID-19 pandemic has affected professional as well as personal lives of physicians. We conducted a survey among Indian physicians to understand this impact.METHODSA 31-point anonymized survey to evaluate the impact of the COVID-19 pandemic and resultant lockdown on physicians' domestic responsibilities was disseminated via e-mail and text messaging applications. Our aim was to evaluate whether the impact was gender-based and to look for differences in aspects of domestic work, childcare, and professional commitments.RESULTSWe obtained 1,041 responses, of which 643 identified themselves as men and 393 as women. An increase in the domestic responsibilities during the lockdown was confirmed by 90% of the women compared with 82% men. More women than men were solely responsible for domestic chores (38.7% v 23.7%), managed their children's education (74% v 31%), and felt an adverse impact of the pandemic on their professional work (60.8% v 42.6%). Fewer women's spouses (57/359) than men's (174/594, P = .00001) were forced to take leave or work reduced hours, and double the proportion of women (3.5% v 1.5%) had to quit their jobs to manage responsibilities at home.CONCLUSIONAs the COVID-19 pandemic and the lockdown measures threw newer challenges, more women physicians than men (81% v 63%) shouldered the burden of increased domestic work and childcare. This survey highlights the need to re-examine the specific challenges faced by women physicians and identify means to support and empower them.